Na trama das aparências : moda e arte na obra de Antoine Watteau (1684 – 1721) - Lima, Laura Ferrazza de (2015)
The present work deals with the relationship between the artistic production of French painter Jean Antoine Watteau (1684 – 1721) and the universe of fashion. Fashion is here presented as a new perpsective to analyze Watteau’s works. The proposed study has a multidisciplinary character, which helps to adress the production of a very complex artist, whose work shows several connections and analogies to other kinds of artistic productions. During her reaearch period in Paris, the author had access to new sources and bibliography, which helped to better understand the way Watteau’s work relates not only to French fashion in the XVIIIth century, but with fashion history as a whole. The work’s mains source is a set of etchings done by different artists, called Figures de Différents Caractères; those images were based on a series of drawings originally done by Watteau. The Figures make up the two first volumes of the Recueil Julienne, a compendium of the artist’s work. Besides the etching, some oil paintings were also studied. Relationships between images produced in the XVIIIth century and images from other temporalities were taken into consideration. The researcher sook to understand the ways clothe and/or fashion impact on the constitution of the artist’s visuality; besides, the work has analysed the construction of memories pertaining clothes and clothings as shown in Watteau’s etchings and paintings; therefore, through the selected images, the researcher has explored the territory occupied by clothes and fashion in te artist’s work. Another element taken into account was the role performed by clothes in the construction of movement and gesture within the selected images. The researcher has investigated which connections can be estabilished between the selected images and the period’s social forms and dress codes. Fashion is a phenomenon characterized by speedy changes and capable of great impact on individuals. Most scholars who adressed that question have pointed the XVIIIth century as the turning point when fashion started to show those characteristics. Watteau’s artistic path has been re-traced here through some biographic data, and his insertion in French culture and society of the XVIIIth century has been investigated; the “survival” of his works in diferent times has also been pondered. The works deals extensively with Watteau’s relationship with theatre and with a genre of painting known as fêtes galantes. The relationship between the selected etchings and French fashion plates has also been examined.